Absentéismo-doença na equipe de enfermagem em um hospital público: doença na equipe de enfermagem em um hospital público - Luciana Brasil Moreira de Oliveira (2014)
This is a study on absenteeism related to diseases affecting the nursing staff in a hospital setting, with the aim of analyzing the rates of absenteeism and illness of the nursing staff of a public hospital in Belo Horizonte for the year 2013. Its ramifications address absenteeism and illness by health care sectors, and time off main pathologies. It is a descriptive and analytical, contemporary documentary research with quantitative approach ends the cross-sectional character. The single case study conducted in a public hospital, large, reference in urgent/emergency use. The population was nursing staff that works in attendance sectors, addressed through census and consists of 1056 professionals, 899 elementary/middle level and top level 157. Data were collected from the hospital database and analyzed with the aid of the Statistical Package for the Social Sciences - version 17 and processed using descriptive statistics and statistical tests (Z and Poisson test). The results show that out of 1056 active employees, 846 had medical licenses (80%). The majority were female (86,4%); between 31 and 40 years (41,8%); belong to auxiliary/technician nurse (84,3%) group; have 4-5 years of working in the hospital (30,8%) and statutory relationship (67,1%). 2.848 medical leave, totaling 19.363 days lost from work were generated in the period. Sectors that showed removals Medical Clinic (267 licenses and 1.402 days lost), Emergency Room (231 licenses and 1.804 days lost) and Intermediate Neonatal Care (215 licenses and 2.196 days lost). In relation to the months of the year there were more licenses in October, April and May and the lowest in December, February and November, and the Z test showed significant differences (p <0.05). As for the duration, most medical licenses are of short duration (up to two days), with 56,6% of the total, the average duration (3-15 days) with 38,6% and of duration longer than 15 days, 4,8%.There was a predominance of repeat presentation of a medical certificate 1-2 times (60,1% of the total). The main conditions of the workers were: diseases of the muscular system and connective tissue (18,5%), diseases of the respiratory tract (14,4%) and Certain infectious and parasitic diseases (9,5%). Absenteeism Index (AI) found for auxiliary/technician was 4,91 for nurses and 5,68 (Poisson test with p-value <0, 01). The IA of urgent/emergency departments was 5,13 versus 4,85 in other sectors of the study (p <0.01). Absenteeism and illness is a contemporary and complex subject and systematic monitoring and evaluation, to be multifactorial and dynamic demands by means of indicators and in association with People Management Policy that aims to improve quality of work life.